Sacred sound and the transcultural practice of Kirtan - Moura, Gustavo H. P. 1975- (Lanham, Maryland: Lexington Books, 2024)
"This book investigates how ideas on sacred sound and the practice of Kirtan are transforming the American religious soundscape. The author approaches Kirtan as a type of 'technology of the self,' which allows people to transform their lives in search for happiness, wisdom, and other types of perfection"--
Includes bibliographical references and index.
Keywords: Kirtana (Hinduism); Hinduism; Religion